The influence of service quality on customer satisfaction - Hendriana, Tengku Ine; Irawan, Nopita (International Journal of Applied Finance and Business Studies, 2024)
This research aims to find out how much influence service quality has on customer satisfaction at the Dimas Jaya Motor (DJM) Workshop in Bandung City. Researchers are interested in researching the effect of service on customer satisfaction because they see the increasing number of customers at the Dimas Jaya Motor repair shop, so this cannot be separated from the service provided by the repair shop. This research uses quantitative methods, the data needed in this research is customer satisfaction data obtained using a questionnaire and tested using SPSS 26. Based on the results of the analysis carried out, there is an influence between service quality on customer satisfaction at the Dimas Jaya Motor (DJM) workshop. which is shown through the regression equation Y = 11.648 + 0.686 The correlation coefficient value between Service Quality and Customer Satisfaction is 0.677, meaning that the relationship between Service Quality and Customer Satisfaction is in the strong category. Meanwhile, the coefficient of determination (R Square) is 0.458 or equal to 45.8%. This figure means that the Service Quality variable (X) simultaneously influences the Customer Satisfaction variable (Y) by 45.8%. Meanwhile, the remainder (100% - 45.8% = 54.2%) is influenced by other variables outside this regression equation or variables that were not studied. The total number of respondents was 112 customers.